O‘SMIRLARDA DAXLDORLIK FAZILATI IJTIMOIY MUAMMO SIFATIDA - Aribjanova, U.A. (SCIENCE and SOCIETY, 2024)
In this article, the psychological characteristics of the manifestation of the quality of involvement in adolescents, including the involvement of students in school education, family customs and reforms, were studied.
Keywords: involvement; education; training; motive; institution; virtue; characteristic; psychological factor; morality; vice; threat; spirituality; enlightenment